Effects and improvements of different reagents preservation methods on the determination of phosphate in seawater by phosphomolybdenum blue spectrophotometric method. (February 2019) - Li, Qiuyu; Zhao, Weihong; Miao, Hui; Han, Xiaotian
Abstract: This work attempted to prolong the validity of the molybdate mixed solution and ascorbic acid solution used in the phosphomolybdenum blue spectrophotometric method by improving their preservation according to the influence factors. The results showed that the molybdate mixed solution can be directly preserved in darkness with validity over half a year. The ascorbic acid solution is influenced by light, temperature, pH, metal ions, oxygen, and bacteria. The validity of ascorbic acid is shortened as the temperature rises. Through keeping in darkness, adding complexing agents, adjusting pH, removing oxygen and sterilization, the validity of ascorbic acid solution was prolonged to over 2.7 times under 4 °C and over 5 times under 25 °C. At the same time, the hybrid solution of ascorbic acid solution and molybdate mixed solution should be preserved separately, otherwise the using effect is poor. Highlights: Meet the current development trend on long-term monitoring of phosphate Improve the reagents preservation methods in phosphomolybdenum blue reaction Prolong the validity of the molybdate mixed solution and ascorbic acid solution Reduce the cost of the reagents replacement in the process of phosphate detection